Loss of Asxl2 leads to myeloid malignancies in mice - Jianping Li; Fuhong He; Peng Zhang; Shi Chen; Hui Shi; Yanling Sun; Ying Guo; Hui Yang; Na Man; Sarah Greenblatt; Zhaomin Li; Zhengyu Guo; et al. (Nature Communications, 2017)
ASXL2 mutations are mostly found in a subset of leukemia patients with certain genetic aberrations; however the role of this protein in normal hematopoiesis and related malignancies is still unclear. Here the authors use a knock-out mouse model to uncover the role of Asxl2in hematopoiesis and leukemogenesis.